Simulation of Connecting Rod Using Finite Element Analysis (International Journal of Innovative Research in Computer Science & Technology, 2018)
Numbers of connected rods are used in the  assembly of petroleum engines, the task of connecting rod  important of converting reciprocating motion of the  piston into rotary motion of the crankshaft. In this work  stress analysis at various individual tensile and  compressive loads acting on connecting rod at different  speed was done. Simulation was performed by using Cero  PTC software to obtain stress distribution in the  connecting rod at static condition.
Keywords: Simulation; Connecting rod; Finite element; Cero PTC; Connecting rod simulation